Pengaruh Islamic Corporate Governance terhadap Kinerja Keuangan Bank Umum Syariah Periode 2017-2021 - Putri Ayu Iffatul Af'idah; Dewi Reni (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2022)
The purpose of this research is to assess the impact of Islamic corporate governance practices on the financial performance of Islamic commercial banks in Indonesia. Islamic corporate governance serves as the independent variable in this study, while financial performance serves as the dependent variable. All Islamic Commercial Banks that are registered with the OJK over the period of 2017–2021 served as the population for this study, which included 15 institutions. The selection of samples methode is using a purposive sampling. With a research time span of five years and nine Islamic commercial banks serving as samples, this study was conducted. The method for analyzing the data is called partial least squares, and the instrument for analyzing the data is called Smart-Pls. In this particular piece of research, a quantitative approach was taken, and secondary data in the form of annual reports submitted by Islamic Commercial Banks were employed as sources of information. According to the findings of this research, Islamic corporate governance has a positive and significant impact on the financial performance of Islamic commercial banks in Indonesia.